Building an Integrated Environmental Care Attitude with Ecopro (Ecobric Product) at SDN 43 Mataram - Arisandi Nirmala; Imam Hamzan Wijaya; Hotimah Hotimah; Neneng Ayu Mulyani; Sarwin Hidayat; Lalu Sumardi; Dadi Setiadi (Lafadz Jaya Publisher, 2024)
This study began with the problems faced, namely the lack of environmental awareness among students of SDN 43 Mataram, especially in plastic waste management. The problems identified in this study include: 1) Suboptimal utilization of plastic waste in the school environment; 2) The lack of environmentally conscious character in students related to waste management; 3) Efforts to instill environmentally conscious character through the use of ecobricks and products from the Pancasila Student Profile Strengthening Project. The purpose of this study was to explain the extent to which ecobrick products can instill environmentally conscious character. This study used a descriptive qualitative method to obtain data on instilling environmentally conscious character through the use of ecobricks at SDN 43 Mataram. Data were collected through student observations, interviews with teachers, and documentation of activities. The results of the study showed that environmentally conscious character can be improved, indicated by the habit of disposing of garbage in its place, using enough water to wash plastic waste, separating plastic waste from other types, and washing hands with soap after activities. In addition to developing environmentally conscious character, this study also showed improvements in other aspects of development, such as fine motor skills, cognition, language, religious and moral values, social emotional, and art. Ecobricks made by students are used as bookshelves and bottle puppets, which are not only useful, but also function as literacy media for students.